Effect of 3 different anticoagulants on hidden blood loss during total hip arthroplasty after tranexamic acid. Issue 36 (4th September 2020) - Deng, Zeng-fa; Zhang, Zi-ji; Sheng, Pu-yi; Fu, Ming; Xu, Dong-liang; He, Ai-shan; Liao, Wei-ming; Kang, Yan
Abstract : Abstract: Comparison of different anticoagulants in blood management and complications with tranexamic acid (TXA) in total hip arthroplasty (THA) is unclear. Our aim was to compare the efficacy and safety among receiving nadroparin calcium, enoxaparin sodium or rivaroxaban after TXA in THA. 150 patients undergoing primary unilateral THA were received 15 mg/kg intravenous TXA (IV-TXA) before skin incision, followed by 1 of nadroparin calcium (Group A), enoxaparin sodium (Group B), or rivaroxaban (Group C) randomly during hospitalization. The primary outcome was hidden blood loss (HBL). Other outcomes such as the maximum hemoglobin (Hb) drop, total blood loss (TBL), the volume of drainage, transfusion rate, length of hospital stay (LOS), and complications were also compared. There were no statistically significant differences in HBL, the maximum hemoglobin (Hb) drop, transfusion rate, and complications among 3 groups. LOS was significantly higher for patients in Group B than Group A ( P = .026). Neither deep venous thrombosis (DVT) nor pulmonary embolism (PE) occurred in any group. There were no differences in efficacy and safety in patients undergoing THA receiving nadroparin calcium, enoxaparin sodium, or rivaroxaban after anti-fibrinolysis with TXA.